Validity and reliability of the Japanese version of the sustainability consciousness questionnaire - Ogishima, Hiroyoshi; Ito, Ayahito; Kajimura, Shogo; Himichi, Toshiyuki (Frontiers in Psychology, 2023)
The sustainable development goals (SDGs) are required to be achieved by 2030, and measurement indicators are needed to properly visualize individual efforts toward SDGs. Here, we developed a Japanese version of the Sustainability Consciousness Questionnaire (SCQ), the most well-known individual measure of SDGs, and examined its reliability and validity. Three online surveys were conducted with 1,268 Japanese adults. The results showed that the Japanese version of the SCQ consists of two single-level factors: sustainability knowingness/attitude and sustainability behavior. These two factors demonstrated sufficient measurement reliability. Additionally, sustainability knowingness/attitude exhibited a negative correlation with positive attitudes toward climate change (holistic affect regarding climate change), and sustainability behavior showed a positive correlation with pro-environmental behavior. These results indicate that the Japanese version of the SCQ is reliable and valid.